2020
DOI: 10.1159/000512180
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Stroke and Ischemic Stroke Subtypes: A Community-Based Study in Brno, Czech Republic

Abstract: <b><i>Background:</i></b> There are few contemporary epidemiological data on stroke for Central Europe. We performed a population-based study evaluating the incidence of stroke, stroke types, and ischemic stroke (IS) subtypes in Brno, the second biggest city in the Czech Republic (CR). <b><i>Methods:</i></b> Using the National Registry of Hospitalized Patients, and hospital databases, we identified all patients hospitalized with a stroke diagnosis in Brno hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…The incidence rate of stroke differs for different types of stroke and similarly to RAO the incidence rate increases with age. 11,12 Aims and/or hypothesis…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of stroke differs for different types of stroke and similarly to RAO the incidence rate increases with age. 11,12 Aims and/or hypothesis…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide epidemiological statistics have indicated that 24.6 individuals per 100,000 experience ICH; these figures are even greater in Asian communities (Weimar and Kleine-Borgman 2017;Haller et al 2019). The rising incidence of ICH is thus an area of global concern (Sedova et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of our ongoing efforts to better characterize the epidemiology of stroke in the Czech Republic [12, 13] in a setting where the estimated burden of stroke is high [1], but resources for large-scale epidemiological projects have been limited. We assess 1-month, 1-year, and 3-year all-cause mortality rates in patients hospitalized with IS in a community-based study in Brno, Czech Republic, in 2011, and identify risk factors predicting short- and long-term mortality after stroke.…”
Section: Introductionmentioning
confidence: 99%